The benefits of integrated pest management for apple depend on pest type and production metrics - Ryalls, James M. W.; Garratt, Michael P. D.; Spadaro, Davide; Mauchline, Alice L. (Frontiers in Sustainable Food Systems, 2024)
The development of integrated pest management (IPM) strategies, aimed at reducing pesticide use, has myriad ecological and agronomic benefits to terrestrial ecosystems and the environment, but can also lead to different biological and economic outcomes depending on the production system. The most common facet of IPM in apple is the reduction and/or alternative use of pesticides but also includes cultural, mechanical and biological controls. Using apple as a model system, we performed a meta-analysis of 55 studies from 20 countries to quantify the effects of IPM on beneficial invertebrates, pest and disease pressure, and crop productivity (i.e., fruit yield and quality). We also explored different feeding guilds (i.e., tissue-chewing, sap-sucking or boring/mining herbivores, and beneficial natural enemy predators or parasitoids) to determine whether invertebrate responses to IPM differ between feeding strategies. By scoring IPM adoption based on the relative number of facets of IPM used in each study, we also determined whether the level of IPM implemented in apple farming systems alters the responses of invertebrates and pathogens. Our results demonstrate how IPM adoption increases the performance of natural enemies, while simultaneously reducing pest and disease pressure overall. However, the effects of IPM on disease pressure may depend on the level of IPM adoption because disease pressure increased when multiple facets of IPM were adopted (i.e., as the level of IPM adoption increased). Apple quality was not limited by IPM adoption, yet fruit yield decreased overall. While both natural enemy feeding guilds (predators and parasitoids) responded positively to IPM adoption, only two of the three pest feeding guilds (tissue-chewing and sap-sucking herbivores) decreased under IPM, with boring/mining herbivores showing no response. These results demonstrate the complex benefits and limitations that can occur under IPM and call for economic risk assessments based on these differences. Effective IPM strategies rely on monitoring practices and pest/pathogen prevention but can provide real environmental value.